Emir Efsahuddin Hidayetullah Beg and his divan : textual analysis, critical edition, facsimile of the Oxford Bodleian Library Or. 76 = Emir Efsahuddin Hidayetullah Bey ve divanı : inceleme, tenkitli metin, tıpkıbasım (Oxford Bodleian Kütüphanesi Or. 76) ([Harvard])
viii, 293 s.